CORRELATION STUDY OF FAMILY ROLES AND PARENTING CULTURE WITH THE INCIDENCE OF STUNTING WITH THE FAMILY CENTERED NURSING APPROACH (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:. At the age of children, it is necessary to fulfill balanced nutrition so that children can grow and develop optimally. The nutritional problem still occurs in children. The data from UNESCO (2020) shows that the number of children with stunting is 149,5 million. The aimed study to analyze the relationship between family roles, parenting culture, and stunting.Methods: This research used correlation analysis with a cross-sectional approach. The independent variable is the role of the family, and parenting culture, and the dependent variable is the incidence of stunting. This study's population was families with toddlers aged (1-5 years) at the Tragah Health Center. Sampling by means of cluster sampling is done based on the assumption that the characteristics of the subjects in each region are the same. In cluster sampling, the sampling unit is the hamlet in the village. The research sample was 42 familiesResults: Based on the results of statistical tests with chi-square, shows that there is a relationship between the role of the family and the incidence of stunting (p-value: 0.000) and there is a relationship between parenting culture and the incidence of stunting (p-value: 0.000).Conclusion: In addition to focusing on the role of family and parenting culture, there are factors that can be intervened to overcome stunting